DAMPAK PEMBELAJARAN DARING DAN LURING PADA MAHASISWA - Djafar, Hamsiah; Muh. Farhan; Muthiah Khaeirunnisa; Nur Padila; Amran Basir (Educational Leadership: Jurnal Manajemen Pendidikan, 2022)
This study aims to analyze how the impact of online and offline learning on students. The research was conducted at UIN Alauddin Makassar with a research sample of 8 active students of the Islamic Education Management Study Program. The type of research used is qualitative research with a descriptive approach. The data collection technique in this study used in-depth interview techniques accompanied by documentation. Data analysis techniques used in the study were carried out in stages of data collection, data reduction, data display and drawing conclusions. The results of the research are discussing the impact of online and offline learning on students’ motivation for learning achievement, in the Islamic Education Management Management Study Program. Online and offline learning has both positive and negative impacts on students bringing a major impact on motivation and student achievement outcomes. In online learning, students are constrained by Internet network connections and limited internet quotas so that it has an impact on decreasing IPK, thereby reducing student learning motivation. Lecturers play an important Role in implementing learning strategies and motivating students to learn. And also students prefer offline learning because it improves the learning process and, it is easier to understand the explanations given by the lecturer directly. With high motivation in learning is associated with high learning achievement, when both learning achievement and learning motivation can work well, we also create learning success in ourselves.